Two new and endangered species of Syngonanthus (Eriocaulaceae) from Chapada dos Veadeiros, Goiás, Brazil - Watanabe, Mauricio Takashi Coutinho; Echternacht, Lívia; Hensold, Nancy; Sano, Paulo Takeo (Phytotaxa, 2015)
We describe and illustrate two new species of Syngonanthus from Chapada dos Veadeiros (Central highlands of Brazil), an area known for its high number of endemic and threatened species, such as those described here. These species have a restricted distribution and inhabit critical areas. Syngonanthus incurvifolius has not been collected since 1994 and is critically endangered; Syngonanthus vittatus is known only from a small somewhat disturbed area, on private property, and is endangered. Evaluation of threatened status was provided by CNCFlora, the IUCN Red List Authority in Brazil.